Nuclear physics : the core of matter, the fuel of stars (National Academy Press, 1999)
Dramatic progress has been made in all branches of physics since the National Research Council's 1986 decadal survey of the field. The Physics in a New Era series explores these advances and looks ahead to future goals. The series includes assessments of the major subfields and reports on several smaller subfields, and preparation has begun on an overview volume on the unity of physics, its relationships to other fields, and its contributions to national needs. Nuclear Physics is the latest volume of the series. The book describes current activity in understanding nuclear structure and symmetries, the behavior of matter at extreme densities, the role of nuclear physics in astrophysics and cosmology, and the instrumentation and facilities used by the field. It makes recommendations on the resources needed for experimental and theoretical advances in the coming decade.
Keywords: Nuclear physics.; Nuclear Physics; Physique nucléaire.; nuclear physics.; SCIENCE -- Physics -- Nuclear.; SCIENCE -- Physics -- Atomic & Molecular.; Nuclear physics; Fisica nuclear.; Nuclear Physics.